2016
DOI: 10.2147/jpr.s113216
|View full text |Cite
|
Sign up to set email alerts
|

Survey of pain specialists regarding conversion of high-dose intravenous to neuraxial opioids

Abstract: The conversion of high-dose intravenous (IV) opioids to an equianalgesic epidural (EP) or intrathecal (IT) dose is a common clinical dilemma for which there is little evidence to guide practice. Expert opinion varies, though a 100 IV:10:EP:1 IT conversion ratio is commonly cited in the literature, especially for morphine. In this study, the authors surveyed 724 pain specialists to elucidate the ratios that respondents apply to convert high-dose IV morphine, hydromorphone, and fentanyl to both EP and IT routes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
0
20
1
Order By: Relevance
“…This IV:EP:IT ratio of 100:10:1 was supported by Krames et al from experience from their practice . In a survey of pain practitioners, Gorlin et al confirmed the use of this conversion ratio when they reported the majority (68%) used IV:EP ratio of 10:1 and (65%) 100:1 IV:IT for morphine conversion . The same ratio was commonly used for converting fentanyl IV to EP and EP to IT as well (40–42%).…”
Section: Discussionmentioning
confidence: 75%
“…This IV:EP:IT ratio of 100:10:1 was supported by Krames et al from experience from their practice . In a survey of pain practitioners, Gorlin et al confirmed the use of this conversion ratio when they reported the majority (68%) used IV:EP ratio of 10:1 and (65%) 100:1 IV:IT for morphine conversion . The same ratio was commonly used for converting fentanyl IV to EP and EP to IT as well (40–42%).…”
Section: Discussionmentioning
confidence: 75%
“…Although there is some uncertainty about equianalgesic dose conversion from IV systemic to epidural opioids, the most commonly cited conversion is 10:1 for both morphine and hydromorphone. [49] Thus, even low dose opioids added to epidural solutions can contribute to a large proportion of the cumulative opioid consumption. Furthermore, the patients would receive this amount of opioid whether they needed it or not.…”
Section: Discussionmentioning
confidence: 99%
“…For purposes of this conversation, we will only discuss the conversion of morphine. It is well accepted that oral to parenteral morphine is a conversion factor of three, parenteral to epidural morphine is a conversion factor of ten, and epidural to IT morphine is a conversion factor of ten [29, 30]. Therefore, when calculating an “equianalgesic dose” of oral morphine to IT morphine, it roughly equates to 1 (oral): 3 (parenteral): 10 (epidural): 10 (intrathecal) or 300 times greater.…”
Section: Discussionmentioning
confidence: 99%